Difficulty with Oral Health Complications in Adolescents with Developmental Disability and Obesity. (July 2023) - Bhoopathi, V.; Wells, C.; Ramos-Gomez, F.; Atchison, K.A.
Introduction: Developmental disabilities (DDs), obesity, and dental caries are highly prevalent health conditions among adolescents. Evidence indicates that a significant proportion of adolescents with DDs are obese, and those with obesity and dental caries share common risk factors. Objective: In this first-ever US-based cross-sectional national study, we assessed the likelihood of adolescents with DDs and obesity experiencing chronic difficulty with decayed teeth, toothaches, bleeding gums, and eating and swallowing due to a health condition among adolescents with DDs and obesity compared to adolescents with no DDs or obesity. Methods: For this secondary data analysis study, we used data of 68, 942 adolescents aged 10 to 17 y from the 2016 through 2019 National Survey of Children's Health. Weighted descriptive and bivariate analyses were conducted. Four multiple logistic regression models predicting chronic difficulty in the past 12 mo with decayed teeth, toothaches, bleeding gums, and eating and swallowing due to a health condition were conducted, controlling for other variables. Results: The adjusted odds ratio (aOR) of experiencing chronic difficulty in the past 12 mo for adolescents with no DDs or obesity was significantly lower for decayed teeth (aOR, 0.64; 95% confidence interval [CI], 0.51–0.80;P < 0.0001), toothaches (aOR, 0.43; 95% CI, 0.30–0.60;P < 0.0001), bleeding gums (aOR, 0.48; 95% CI, 0.33–0.70;P < 0.0001), and eating or swallowing due to a health condition (aOR, 0.34; 95% CI, 0.20–0.57;P < 0.0001) compared to adolescents with both DDs and obesity. Conclusions: Results from this study indicate that DD adolescents with obesity have more/greater impending oral health needs than adolescents with no DDs or obesity. Knowledge Transfer Statement: Results of this study highlight the high oral health needs and the chronic difficulty adolescents with developmental disabilities and obesity experience compared to adolescents without developmental disabilities and obesity. Targeted oral health policies and interventions that will promote oral health among this high-risk group are recommended.